Influence of Generative Artificial Intelligence on HR Practices:The Role of Innovation Climate (Journal of Asian Development Studies, 2024)
This research uses the Socio-Technical Systems (STS) theory postulating that organizationalsuccess is a product of social and technical sub-systems, and examine the effects of generative AIon the HR practices. Furthermore, the study focuses on the mediating role of innovation climateon the relationship between generative AI and HR practices in the hospitality sector. A sample of327 participants is selected by a convenient sampling technique from hotel employees. The data iscollected through structured questionnaire and analyzed using PLS-SEM. The results of the studybring essential insights into the interactions between technological dynamics and organizationalenvironments in the case of HR functions in the technology oriented world. Findings shows thatgenerative AI has a massive positive impact on the HR practices and innovation climate positivelyinfluence HR Practices. This finding supports the notion that Innovation Climate mediate therelation between generative AI and HR practices. The findings imply that generative AI improvesHR Practices but that its full potential is unlocked with a robust innovation climate. The study’sfindings contain practical and managerial implications for professionals, managers, and leadersas well as policymakers who desire to improve HR practice and create an innovative environmentusing generative AI. To attain benefits, HR leaders need to spend as much as they can on the AIdriven tools which is capable of doing these processes but handles HR teams to work together tobenefit from AI.